Struktury religijne na przykładzie „Atlasu wyznań i religii w Rzeczypospolitej w drugiej połowie XVIII w.” - Szady, Bogumił (Studia Geohistorica, 2017)
The present article deals with harmonization of selected geographical and historical information on territorial structures of religions and denominations in the 18th century Polish-Lithuanian Commonwealth and their cartographical presentation. It refers to two categories constituting the content of the map, namely churches and units of territorial administration of particular religions. The Author focuses on problems concerning interpretation of written and cartographic sources as well as the methods of transferring those interpretations onto the cartographic form, which requires precision and accuracy. He indicates the criteria for the qualification of sacral places (in the formal and functional-architectural aspects) which detertheir inclusion in “Atlas of Religions and Confessions in the Polish-Lithuanian Commonwealth in the 2nd Half of the 18th Century” Referring to the tradition of the existing cartographic forms, the Author discusses the categories of sacral places and the methods of presenting them in the main map in the scale 1:300 000. In the case of borders, the Author focused attention on the problem of harmonization of territorial structures of the Latin, Lutheran and Jewish denominations. The conclusion emphasizes the necessity for generalization and simplification of the presented phenomena which the recipient of cartographic presentations should be aware of. At the same time, the Author indicated a need for reliable information to be reflected in a content-related commentary and an index including the source basis and all kinds of remarks concerning the map.